2016
DOI: 10.1039/c6ra19635g
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and direct analysis of multiple types of organic contaminants in water based on a MOF decorated with a suitable quantity of Au nanoparticles, using SALDI-TOF MS

Abstract: Due to intensive industrial growth, water has become more and more polluted with toxic organic contaminants, which pose a great threat to human health and water ecosystems. Developing advanced multi-residue methodologies can provide broad and realistic information about water pollution in a rapid, sensitive and selective way. Mass spectrometry (MS) coupled with gas chromatography (GC) or liquid chromatography (LC) has been successfully applied for identifying and analyzing multiple types of analytes in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Multiple mechanisms are possible for PFOS adsorption to UiO-66, including Lewis acid–base complexation or electrostatic adsorption of the sulfonate headgroup of PFOS to the Zr 4+ CUS in defective UiO-66, ion-exchange between the charge compensating Cl – and the sulfonate headgroup, hydrophobic interactions between PFOS and the bdc linker molecules, and hydrogen bonding between PFOS and Zr-coordinated water. , In this system, we hypothesize that electrostatic interactions with Zr 4+ and/or hydrophobic interactions are most likely. Lewis acid–base complexation (i.e., chemisorption) between the Zr 4+ CUS and the sulfonate headgroup of PFOS was ruled out via the FTIR spectra of the MOFs after adsorption (Figure S3b).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Multiple mechanisms are possible for PFOS adsorption to UiO-66, including Lewis acid–base complexation or electrostatic adsorption of the sulfonate headgroup of PFOS to the Zr 4+ CUS in defective UiO-66, ion-exchange between the charge compensating Cl – and the sulfonate headgroup, hydrophobic interactions between PFOS and the bdc linker molecules, and hydrogen bonding between PFOS and Zr-coordinated water. , In this system, we hypothesize that electrostatic interactions with Zr 4+ and/or hydrophobic interactions are most likely. Lewis acid–base complexation (i.e., chemisorption) between the Zr 4+ CUS and the sulfonate headgroup of PFOS was ruled out via the FTIR spectra of the MOFs after adsorption (Figure S3b).…”
Section: Resultsmentioning
confidence: 95%
“…The TGA and pore size distribution data implicate that UiO-66-25 is missing more linkers than UiO-66-10 (Figure S2, Figure d), and therefore is likely more hydrophilic. Increased framework hydrophobicity has been demonstrated to be beneficial for the adsorption of PFASs onto UiO-66-based materials, indicating that the right balance between increased amount of Zr CUS sites and decreased hydrophobicity (as functions of structural defectiveness) can improve the adsorption properties for PFOS and other perfluorinated compounds. , …”
Section: Resultsmentioning
confidence: 99%
“…To overcome the interference from Au cluster peaks and poor reproducibility, Niu et al [ 115 ] synthesized an Au NP-loaded Zr based MOF by using functionalized amino groups (UiO-66-NH 2 @Au) and used as adsorbent of solid phase extraction (SPE) as well as matrix for LDI-TOF MS. Since the strong affinity to organic pollutants of UiO-66-NH 2 @Au, perfluorinated chemicals including perfluorobutane sulfonate, perfluorohexane sulfonate and PFOS, the endocrine disrupting chemical bisphenol A (BPA), halogenated flame retardants including TBBPA, pentabromophenol and tetrachlorobisphenol A, the pesticide PCP, and hormones including l -thyronine, l -thyroxine and 17-aethynylestradiol at different levels were successfully identified by LDI-TOF MS in negative mode with the assistance of UiO-66-NH 2 @Au.…”
Section: Nanomaterial-assisted Ldi For the Analysis Of Environmentmentioning
confidence: 99%
“…Besides, the benzene structures in such MOFs can form p-p interactions with aromatic substances. 20 It have been reported that some ame retardants can be encapsulated in MOFs, 21,22 but the amount of relevant studies is still limited. Li et al 23 found that MIL-based MOFs showed the effective adsorption of a typical brominated ame retardant, hexabromocyclododecane, from aquatic environment via hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%